The food chain of YouTubers: engaging audiences with formats and genres - Himma-Kadakas,Marju (2018)
Traditional news media are not engaging young audiences and there has been a decline in the number of consumers of traditional media. The main news sources for teenagers in Europe and North-America are social media and friends. Our research project outlines YouTubers content production strategies in order to apply them in conventional news content production to attract young audiences. In this study we profiled the top YouTubers in the world, in Europe and in Estonia based on their profiles, networks, topics, genres and formats. We developed a model of analysis based on the uses and gratifications approach by Katz et al. (1974), and McQuail (2000). This framework was used in the standardised content analysis of YouTube videos. The results present the food chain of different levels of YouTubers; the food chain refers to the copying of innovative ideas from less experienced peers, while promoting their content. The food chain also shows how most popular YouTubers generate new production practices and discursive genres. There are noticeable variations in the diversity of genres and formats between different levels of YouTubers. Diversity of content is important for sustaining and increasing audiences. YouTubers utilise specific combinations of genres and formats for certain topics across levels of the food chain. This makes it possible to develop a typology of techniques that YouTubers use to engage audiences.